PWE-038 Adalimumab therapy for infliximab failures in Crohn's disease. A single-centre UK experience. (23rd September 2015) - Sprakes, M B; Ford, A C; Warren, L; Greer, D; Donnellan, C F; Jennings, J S R; Everett, S M; Hamlin, P J
Abstract : Introduction: Adalimumab (ADA) is efficacious in Crohn's disease (CD) patients who have lost response to infliximab (IFX).1 However, there are little data detailing the long-term follow-up of IFX failures who are receiving ADA. Our aim was to prospectively analyse long-term outcomes of CD patients treated with ADA as a second line anti-TNF agent in Leeds. Methods: CD patient data include demographics, previous IFX regime, reason for IFX discontinuation, disease site, immunomodulator and steroid use, Harvey-Bradshaw indices (HBI), BMI and adverse events. Results: Since 2007, 36 CD patients (previously treated with IFX) received ADA in Leeds. 27 females (75%). Mean age 36. 21 had luminal disease (58%), 15 had fistulating disease (42%) 88% of these having perianal fistulae. 16 previously received IFX in a scheduled manner (44%), 11 episodically (31%), with nine switched to scheduled IFX to try and improve response, and nine had three dose induction of IFX only (25%). 22 patients received induction ADA dosing of 80 mg/40 mg (61%), 14 received 160 mg/80 mg (39%). Response was assessed following four injections. 27 patients initially responded (75%) with sustained response in 22 (58%), median follow-up of 12 months. Eight patients were primary non-responders (NR) to ADA, four of whom were primary NR to IFX. One discontinued during ADA induction due to a reaction. Other reasons for discontinuation were: 3 secondary NR, 1 further reaction, 1 patient in remission. The outcomes for patients who discontinued therapy were as follows: 10 patients had surgery (71%), 4 were observed (29%). 20 patients were on steroids prior to ADA therapy (55%), 10 were on steroids at follow-up (28%) with seven patients able to decrease the steroid dose. The mean HBI on commencing ADA was 10.7 and 7.1 after four injections. In 23 responders (four excluded as stoma) the HBI was 10 pre ADA and 5.5 after four injections, with 12 (52%) having HBI of <4 (defined as remission). In primary NR the HBI was 14.2 pre ADA and 12.4 on discontinuation. There were seven reactions attributed to ADA, two requiring cessation of therapy. Three were localised skin reactions at the injection site, and two diffuse skin rashes. There was one opportunistic infection (HSV). Conclusion: ADA is a safe and effective therapy in CD patients who have been exposed to IFX. Our data demonstrate a good initial response to ADA and a sustained response out to 12 months of therapy. Steroid sparing was achieved in 50% of patients and few adverse events have been documented. These data confirm the efficacy of ADA use in IFX failures in a single centre UK experience.